SHM_415476_HST_3D Thin-Butted Stone Axe - Hagaeus, Thomas; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a thin-butted stone axe from the Swedish Early Neolithic, collected in Sweden and held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=410

Link to Sök I Samlingarna

https://samlingar.shm.se/object/AED66DB3-3B57-48B3-BC7D-D5044272430B
Keywords: Archaeology; Archaeology; Archaeology/history; History and archaeology; Photogrammetry; Dynamic Collections; 3D Model; Museum Object; Swedish Early Neolithic; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi